2016
DOI: 10.1021/acsomega.6b00085
|View full text |Cite
|
Sign up to set email alerts
|

Charcoal Disrupts Soil Microbial Communication through a Combination of Signal Sorption and Hydrolysis

Abstract: The presence of charcoal in soil triggers a range of biological effects that are not yet predictable, in part because it interferes with the functioning of chemical signals that microbes release into their environment to communicate. We do not fully understand the mechanisms by which charcoal alters the biologically available concentrations of these intercellular signals. Recently, charcoal has been shown to sorb the signaling molecules that microbes release, rendering them ineffective for intercellular commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 43 publications
(116 reference statements)
3
34
0
Order By: Relevance
“…Previously, we showed that PyOM triggers a significant decrease in the bioavailability of one class of diffusible signaling molecules used for microbe-microbe communication (acyl homoserine lactones) due to both sorption and pH-dependent hydrolysis (13). To test whether these effects were specific to maple and compost or other PyOM types enhance flavonoid signal reduction, we evaluated the effects of PyOM derived from three different POC plant types (yard waste, wood waste, and oak wood) on naringenin availability before and after pyrolysis ( fig.…”
Section: Plant-derived Organic Matter Causes the Largest Flavonoid Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we showed that PyOM triggers a significant decrease in the bioavailability of one class of diffusible signaling molecules used for microbe-microbe communication (acyl homoserine lactones) due to both sorption and pH-dependent hydrolysis (13). To test whether these effects were specific to maple and compost or other PyOM types enhance flavonoid signal reduction, we evaluated the effects of PyOM derived from three different POC plant types (yard waste, wood waste, and oak wood) on naringenin availability before and after pyrolysis ( fig.…”
Section: Plant-derived Organic Matter Causes the Largest Flavonoid Lossmentioning
confidence: 99%
“…Greater OC contents are typically thought to enhance plant productivity and symbiotic interactions (12), but it is unknown whether OC directly influences the bioavailability of plant-microbe signals. Among the possible mechanisms through which OC and the soil matrix may abiotically influence signal availability, sorption onto particulate OC (POC) and reactions with dissolved OC (DOC) could play roles in modifying plant-microbe signal transmission (13). As various flavonoids have distinct chemical properties and functional groups, these mechanisms have the potential to differentially affect flavonoid movement through the soil matrix.…”
Section: Introductionmentioning
confidence: 99%
“…When the environment pH raised from acidity to alkalinity, the lactone ring of the signal molecules used by microbes for quorum sensing was prone to ring-opening hydrolysis, which caused inactivation of AHL molecules (Fig. 4) (Byers et al 2002;Gao et al 2016;Yates et al 2002). Short-chain AHLs are more prone to hydrolysis than long-chain AHLs; therefore, the hydrolysis in a given local environment will change the patterns of signal molecules (Yates et al 2002).…”
Section: Biochar-microbe Interactionsmentioning
confidence: 99%
“…Short-chain AHLs are more prone to hydrolysis than long-chain AHLs; therefore, the hydrolysis in a given local environment will change the patterns of signal molecules (Yates et al 2002). Because of the presence of inorganic phase (ash), the amendment of biochar generally increases soil pH, which may induce hydrolysis of quorum sensing signal molecules, and consequently change the microbial community structure (Gao et al 2016). The pH-dependent hydrolysis is reversible when pH was adjusted to < 2, yet prolonged incubation times were required to recyclize the HSL rings (Yates et al 2002).…”
Section: Biochar-microbe Interactionsmentioning
confidence: 99%
“…These effects can be direct, through mechanisms such as AM fungal colonization of the biochar, enabling access to nutrients adsorbed to the biochar (Hammer et al ), and potentially the alteration of plant‐AM fungal signaling molecules (Warnock et al ). However, biochar can also indirectly affect AM fungi through the sorption or degradation of cell–cell signaling molecules from bacteria (Masiello et al ; Gao et al ) that may affect cycling of phosphorus or other nutrients (Warnock et al ). Despite these potential effects, there are relatively few studies testing the interaction between soil biochar amendments and AM fungi outside of an agricultural setting, and these have found variable outcomes (e.g.…”
Section: Introductionmentioning
confidence: 99%